2020
DOI: 10.2147/ndt.s238286
|View full text |Cite
|
Sign up to set email alerts
|

<p>Identifying Suicidal Ideation Among Chinese Patients with Major Depressive Disorder: Evidence from a Real-World Hospital-Based Study in China</p>

Abstract: These authors contributed equally to this work Background: A growing body of research suggests that major depressive disorder (MDD) is one of the most common psychiatric conditions associated with suicide ideation (SI). However, how a combination of easily accessible variables built a utility clinically model to estimate the probability of an individual patient with SI via machine learning is limited. Methods: We used the electronic medical record database from a hospital located in western China. A total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 54 publications
3
21
0
Order By: Relevance
“…XGBoost-2 resulted from adding features of cognitive function (SST, IGT) to XGBoost-1. Our ML classifiers presented relatively good performance in the task of classifying suicide attempters in MDD patients in accordance with previous studies that used shallow or deep learning algorithms [ 17 , 36 , 37 ]. According to the statistical indicators, ROC curve, DCA, and NRI, when cognitive function was incorporated into XGBoost model, it exhibited improved model fit and superior predictive accuracy and improved patients net benefits, while maintaining the same level of sensitivity for DSA.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…XGBoost-2 resulted from adding features of cognitive function (SST, IGT) to XGBoost-1. Our ML classifiers presented relatively good performance in the task of classifying suicide attempters in MDD patients in accordance with previous studies that used shallow or deep learning algorithms [ 17 , 36 , 37 ]. According to the statistical indicators, ROC curve, DCA, and NRI, when cognitive function was incorporated into XGBoost model, it exhibited improved model fit and superior predictive accuracy and improved patients net benefits, while maintaining the same level of sensitivity for DSA.…”
Section: Discussionsupporting
confidence: 87%
“…Some ML algorithms have been developed to build suicide predictive models, using methods such as Decision Tree, Support Vector Machine, Random Forest, Naïve Bayes, and Artificial Neural Network [ 15 , 16 ]. The current suicide attempt predictive models were developed mostly based on demographics, clinical information, and biological variables [ 17 ]. Most models recognized that childhood trauma [ 18 , 19 ], impulsivity, and aggression [ 2 , 20 ] were risk factors for suicide attempts [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study suggested that the lifetime prevalence of MDD patients related to SI is estimated to be 53.1% 4 . Therefore, SI is regarded as a red alert and maybe the primary predictor for suicide in MDD patients 5 . Although several sensitive brain regions in MDD patients in relation to SI have been identified across several decades of research 6 , 7 , knowledge about whole brain structural network basis associated with SI is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Eligible patients were those with a diagnosis of MDD, aged between 18 and 65. In this study, we identified MDD patients through recorded primary diagnosis at discharge and based on the International Classification of Disease, Tenth Revision (Clinical Modification Codes F32, single episode major depressive disorder and F33, recurrent major depressive disorder), which has been described in another study ( 35 ). We extracted anonymous clinical-related information.…”
Section: Methodsmentioning
confidence: 99%